RIICE development in Cote d’Ivoire : AfricaRice report of 2024. Transforming Agrifood Systems in West and Central Africa Initiative (TAFS-WCA) - Yéo Yassongui, Serge-Alin; Kouadio, Kouamé Serge Alain; Elliott, Dossou-Yovo; Ouedraogo, Mathieu; Singh, Manjari (2024)
Côte d'Ivoire has significant potential for rice production, yet the country remains heavily reliant on imports due to low yields and limited adoption of improved technologies. Climate change further exacerbates these challenges, affecting rice productivity and food security. The Remote Sensing-based Information and Insurance for Crops in Emerging Economies (RIICE) decision support system was introduced to provide reliable, real-time data on rice cultivation, yield forecasts, and climate-related risks. This report details activities conducted by AfricaRice in 2024 related to the adaptation and implementation of the RIICE tool in Côte d'Ivoire through field experiments, georeferencing of rice fields, and the collection of leaf area index (LAI) data as well as feedback from stakeholders to ensure the tool is co-designed, responds to the local needs and that challenges related to infrastructure requirements and capacity building are addressed in the road for institutionalization. The findings highlight the potential of RIICE to enhance rice sector planning, improve resilience among smallholder farmers, and support policy decisions for achieving rice self-sufficiency.